2008
DOI: 10.1017/s0954102007000910
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuation history of the interior East Antarctic Ice Sheet since mid-Pliocene

Abstract: Cosmogenic 10 Be and 26 Al measurements from bedrock exposures in East Antarctica provide indications of how long the rock surface has been free from glacial cover. Samples from the crests of Zakharoff Ridge and Mount Harding, two typical nunataks in the Grove Mountains, show minimum 10 Be ages of 2.00 AE 0.22 and 2.30 AE 0.26 Ma, respectively. These ages suggest that the crests were above the ice sheet at least since the Plio -Pleistocene boundary. Adopting a 'reasonable' erosion rate of 5 -10 cm Ma -1 increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 38 publications
(66 reference statements)
3
10
0
Order By: Relevance
“…Table 1 gives the cosmogenic 10 Be, 26 Al and 21 Ne concentrations for the samples. Concentrations of 10 Be and 26 Al in R9201 and R9204 were also measured in our earlier study (Huang et al, 2008). The two samples were prepared and determined again and the concentrations of 10 Be and 26 Al obtained in this study are consistent within 10% to those reported in Huang et al (2008).…”
Section: Sample Preparation and Measurementsupporting
confidence: 75%
See 1 more Smart Citation
“…Table 1 gives the cosmogenic 10 Be, 26 Al and 21 Ne concentrations for the samples. Concentrations of 10 Be and 26 Al in R9201 and R9204 were also measured in our earlier study (Huang et al, 2008). The two samples were prepared and determined again and the concentrations of 10 Be and 26 Al obtained in this study are consistent within 10% to those reported in Huang et al (2008).…”
Section: Sample Preparation and Measurementsupporting
confidence: 75%
“…In an earlier study, we determined bedrock exposure ages in the Grove Mountains, East Antarctica, with the cosmogenic nuclides 10 Be and 26 Al (Huang et al, 2008). The 10 Be-inferred minimum exposure ages for the crests of the Zakharoff Ridge and Mount Harding, two typical nunataks in the Grove Mountains, are 2.0 Ma and 3.89 Ma, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The crest is 2300 m a.s.l., 200 m higher than the current ice sheet level. Detailed geological and geomorphic descriptions can be found in Huang et al [4]. The two samples R9202 and R9203 studied in this work were taken from smooth granulite bedrock, which are 8 and 15 m below the crest.…”
Section: Preparation Of Samples From the Grove Mountainsmentioning
confidence: 99%
“…Cosmogenic radio-nuclides are normally determined with AMS, and radio-nuclides with long half-life such us 10 Be, 26 Al can be used to date exposure age [4] and burial age [5,6] up to million years. For exposure ages over 3-5 Ma, the concentrations of 10 Be and 26 Al are close to saturation, thus they cannot provide precise ages.…”
mentioning
confidence: 99%
See 1 more Smart Citation